Corporate governance and finance - Hirschey, Mark; John, Kose; Makhija, Anil K. (Advances in financial economics ;, 2003)
Papers in this volume focus upon corporate governance, broadly defined as the system of controls that helps the corporation effectively manage, administer and direct economic resources. Questions of what and how to produce become equally important as organizations strive to better serve demanding customers. As a result, the design and control of effective organizations structure has been described by the vertical and horizontal relationships among the firm, its customers and suppliers. More recently, researchers have come to understand that the efficiency of firms depends upon the ability of participants to find effective means to minimize the transaction costs of coordinating productive activity. As financial economists have learned, resource allocation will be efficient so long as transaction costs remain low and property rights can be freely assigned and exchanged. An important problem that must be addressed is the so-called agency problem resulting from the natural conflict between owners and managers. Agency costs are the explicit and implicit transaction costs necessary to overcome the natural divergence of interest between agent managers and principal stockholders. The value-maximizing organization design minimizes unproductive conflict within the firm. Papers in this volume show how corporate control mechanisms inside and outside the firm have evolved to allocate decision authority to that person or organization best able to perform a given task.